Propuesta de implementación de un Sistema de Control Interno para la eficiencia y eficacia en las operaciones del área de caja y bancos de la Empresa Comercializadora de Hidrocarburos MVG Combustibles SAC - Cueva Mas, Pedro Daniel (2012)
An Internal Control System provides greater control and security to the optimal utilization of the resources of the company and in this way, it looks for the greater effectiveness and efficiency in the operations which it is performed. If an organization of medium size does not adopt a sound Internal Control System, exclusively in the area of Cash and Bank, the Treasury department would suffer very soon and remarkably negative effects that this absence produces. The reasons why they are not carried out in many organizations can be many; among them: the fear of change, insecurity, bad experiences, among others. The feasibility to implement a system of Internal Control is possible; always and when taken into account the aspects necessary in an organization. The retailer MVG Combustibles SAC, will be studied for the present work, where we will determine if the proposal for implementation of an Internal Control System is to improve the efficiency and effectiveness in operations in the area of cash and bank. In addition to ascertain the reasons for which the company has not yet adopted a system of Internal Control defined, as well, the consequences of not doing so and the feasibility for being able to implement them.